Development of a Motor–Neural Testing System Using Motion-Tracking Technology to Measure Skill Response Speed in Volleyball for Youth Players - Faihan, Amer (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The researcher used an experimental method using a design of two equivalent groups with pre- and post-tests, as it is appropriate for the nature of the problem and aligns with the objectives of the study. The research population consisted of youth volleyball players aged (12–16 years) registered in the sports academies of Al-Anbar Sports Club, totaling (16) players. The most important conclusions were that the motor–neural exercises used in the training program significantly improved the skill response speed of the experimental group, which was reflected in their performance on the post-tests, particularly in the moving-ball response test. The motion-path tracking exercises enhanced motor accuracy and visual–motor coordination among the experimental group, leading to better execution of fundamental volleyball skills.